Sidelobe reduction of large‐scale antenna array for 5G beamforming via hierarchical cuckoo search. Issue 16 (1st August 2017) - Sun, Geng; Liu, Yanheng; Li, Jionghui; Zhang, Ying; Wang, Aimin
Abstract : Large‐scale antenna array (LSAA) is one of the key factors as well as a fundamental technology in fifth generation wireless communication systems. Beampattern sidelobe (SL) suppressing is a complex nonlinear optimisation problem, especially for LSAAs, because of the high‐dimensional solution space. A SL reduction method for LSAA based on a hierarchical cuckoo search (HCS) algorithm is proposed. HCS divides the candidate solutions into different levels to improve population utilisation, so that it is suitable for dealing with large‐scale elements. The effectiveness of the proposed method for synthesis of the beampattern of LSAA is verified by theoretical and EM simulations.